C-Type Natriuretic Peptide Ameliorates Lipopolysaccharide-Induced Cardiac Dysfunction in Rats with Pulmonary Arterial Hypertension. (20th December 2018) - Gao, Xiaowei; Zhu, Maoen; Cao, Yanan; Yang, Yue; Ye, Zhi; Zhang, Fan; Guo, Qulian; Peng, Yonggang; Wang, E.
Abstract : Lipopolysaccharide induces rapid deterioration of cardiac function in rats with pulmonary arterial hypertension. It was desired to investigate if this cardiac dysfunction could be treated by C-type natriuretic peptide. Rat pulmonary arterial hypertension was induced by intraperitoneal injection of monocrotaline. Hemodynamics and cardiac function were measured by pressure-volume (P-V) catheter before and after the rats were treated with lipopolysaccharide and C-type natriuretic peptide. Cyclic guanosine 3′, 5′-monophosphate (cGMP) level was determined by enzyme-linked immunosorbent assay analysis. After the rats were injected with low-dose lipopolysaccharide, they experienced left ventricle systolic function deterioration. Administration of C-type natriuretic peptide improved hemodynamics and left ventricle systolic function. cGMP level was elevated after C-type natriuretic peptide treatment. C-type natriuretic peptide could ameliorate lipopolysaccharide-induced cardiac dysfunction and restore hemodynamic deterioration in rats with pulmonary arterial hypertension.